Penggunaan Model UTAUT Dalam Menganalisis Minat Masyarakat Menggunakan Quick Response Code Indonesian Standard (QRIS) Sebagai Alat Pembayaran Digital - Herniah Herniah; Benget Hutagaol (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2025)
Quick Response Code Indonesia (QRIS), is a form of integration of various types of QR originating from various PJSP (Payment System Service Providers) with the application of the QR Code developed by Bank Indonesia in collaboration with the Indonesian Payment System Association. The application of this payment method aims to integrate all non-cash transactions in Indonesia. QRIS can be used in all payment applications owned by PJSP both bank and non-bank types. This study aims to analyze the factors that influence Merchant interest in using QRIS as a digital payment tool based on factors in the Unified Theory of Acceptance and Use of Technology (UTAUT) model. UTAUT can help in understanding user behavior related to the acceptance and use of mobile applications or e-commerce platforms. This research uses primary data by distributing questionnaires to 100 respondents. The respondents in this study were QRIS merchants. To analyze the data, the authors used Multiple Linear Regression Analysis. The results of this study indicate that the performance expectation variable (X1), the business expectation variable (X2), social influence (X3) and facilitating conditions (X4) have a positive effect on Merchant interest in using QRIS as a digital payment tool. The variable that has the most dominant effect is the business expectation variable (X2).